Christianity between Capitalism and Socialism - Robert Bogešić (Kairos (English Ed.))
Modern society is in an unsustainable state. There is a crisis in our political systems, economies, finances and, what is worse, in our morals and value standards. On one side, American capitalism is burdened with the struggle for profit and social justice, and on the other, Europe is burdened with a grand unifying project as a way of building stability and security. Where is the Christian church in all of this? What does Christianity offer? Is there a Christian socialism? Regardless of how the system is named – be it capitalism, socialism or something else - only a system without the basic objective of profit maximization, one that does not consume resources to the point of their exhaustion, beyond its borders, one which is not based on greed, only considering its own well-being, and that does not blame others for its mistakes, but the one that is aware of its neighbor, only that one has a future.